Transposing from screen to stage : creating and implementing an analitical framework for incidental music during a theatre production - Bezuidenhout, Stephanus Abraham (Stellenbosch : Stellenbosch University, 2017)
Thesis (MDram)--Stellenbosch University, 2017.